Mastery of fundamental movement skills among children in New South Wales: prevalence and sociodemographic distribution - Okely, A. D.; Booth, M. L. (Journal of Science and Medicine in Sport, 2004)
Fundamental movement skills form the foundation for many of the specific motor skills employed in popular sports and leisure activities. Little data exist on the prevalence and socioeconomic distribution of fundamental movement skill mastery among young children in Australia. This study process-assessed performance on six fundamental movement skills in a randomly selected sample of students from Years 1 through 3 in the Sydney metropolitan area of New South Wales. The prevalence and sociodemographic distribution of mastery and near mastery for each skill and each skill component is reported for boys and girls in each school year. The findings revealed that the prevalence of mastery and near mastery of each of fundamental movement skill was generally low. Boys performed significantly better than girls in the run and in the four object-control skills (throw, catch, kick, and strike) whilst girls performed better than boys in the skip. There was no consistent association between prevalence of skill mastery and socio-economic status (SES), with only the kick and vertical jump for boys and catch, dodge, and vertical jump for girls differing across SES tertiles. Based on these results, we recommend that adequate curriculum time, resources, and professional development continue to be devoted to fundamental movement skills in NSW primary schools.